Urban ravine territories as a resource of formation of the recreational framework of the metropolis (on the example of Volgograd) - Чапайкин, А. М.; Антюфеев, А. В (Sot͡s︡iologii͡a︡ goroda, 2023)
The article considers the problem of insufficient number of urban recreational areas of Volgograd, the solution of which can be an increase in recreational areas due to the quality development of the urban ravines territories. On the basis of the analysis of the world experience, the main tendencies of formation of public spaces in the civil-urban areas have been identified. The role of such territories in urban development of Volgograd and their influence on its planning structure has been analyzed. On the example of Volgograd formulated and illustrated key provisions of the organization of the system of recreational public spaces on riversides into a single recreational urban framework. The stages of development of design solutions and recommendations on the formation of recreational public spaces on the urban ravines territories have been proposed. An analysis of the existing landscape and town-planning structure of Volgograd is presented, on the basis of which, as an illustration of the provisions, two architectural and town-planning concepts of recreational public spaces on the urban ravines territories were developed, as examples of territories with the greatest and least anthropogenic interference